Synodality as a return to the origins of Christianity and the way of building the God’s Kingdom - Sebastian Zygmunt (Warszawskie Studia Teologiczne)
Over the centuries, exercising authority in the Catholic Church had been generating many doubts and problems. The extreme understanding the Pope’s role as an absolute monarch who independently decides about all dimensions of the Church has supplanted with time the known from the Apostle’s time communal management of the Mystical body of Christ. Just the Second Vatican Council and the last few popes noticed this particular problem. And one of the given solutions was the necessity of the return to the former way of exercising power by the college of bishops united around the Saint Peter’s Successor. Synods whose provisions would be presented to the Bishop of Rome for possible corrections and acceptance could again become a tool of power. By the analysis of the patrology research results, the history of the Catholic Church and dogmatic theology as well as sources and the subject literature it was possible to answer the question what synodality is in general, where does it draw its foundations and what is its role in building of the Kingdom of God. It was also possible to outline the perspective of the further Church development in an increasingly globalised world. The reflection on the historical formation of a proper understanding of collegiality and primacy proved helpful in understanding the goals behind the ”decentralization” of power in the Church postulated today by Pope Francis.